REDUCED INEQUALITIES (SDG10) THROUGH EMPLOYEES’ ENGAGEMENT AND CORPORATE CULTURE - Ling, Chow Poh; Qian, Rachel Ham Rui; Amy, Yeo Chu-May (Graduate Program of Universitas Tarumanagara, 2025)
As part of the 2030 Agenda for Sustainable Development, reduced inequalities (SDG Goal 10) are essential for attaining sustainable development through an all-encompassing and integrated approach, with cooperative effects from organisations and academic institutions. This study intends to examine the influencing factors on firm engagement with reduced inequalities, which is Goal 10 from the SDGs. Thus, employee engagement, corporate culture and adoption of artificial intelligence, are adopted as the variables that would affect firm engagement with reduced inequalities.